Deep Marine Turbiditic Belaga Formation of Late CretaceousâLate Eocene in Central Sarawak, Malaysia: Implications for Sediment Transport and Distribution of Total Organic Carbon (TOC) - Ahmed, N. (Slovnaft VURUP a.s, 2021)
Turbiditic black shale samples were collected from the fresh road-cuts and outcrops of Late Cretaceous to Late Eocene Belaga Formation of Rajang Group from Central Sarawak, East Malaysia. The samples were analyzed for their total organic content (TOC) using Eltra CS800 (Carbon-Sulphur determinator). The main objective of this study is to categorize and pinpoint the distribution of organic matter content for these deep marine turbiditic shales and to relate them with the depositional setting. The results show that the overall values of TOC for all five members of the Belaga Formation range from 0.14 to 7.22 wt. Sandy or silty fine-grained shales have low values of total organic content, while higher values are recorded in blackish finer-grained mudstone/shale beds. In Layar Member, for shales belon-ging to the distal plain or lobe fringe environment, the TOC values vary from 0.29 to 1.39 wt. For Kapit Member, which belongs to the distal lobe or distal lobe fringe, with few having features matching to that of crevasse splay deposits, the range of TOC values is from 0.14 to 2.37 wt.. The samples from the Pelagus Member displayed a greater and broader range of TOC values ranging from 0.32 to 7.22 wt.. Owing to the fact that the sediments went through a large distance during the phase of transportation prior to deposition, which resulted in the low TOC values of the studied samples. Furthermore, oxidation of the organic matter occurs by the transport of sediments through long-shore waves or turbidity flows. Low-energy sediments have a higher organic carbon preservation potential. The TOC values from older stratigraphic members toward younger members are declining considerably, which suggests a corresponding decrease in organic content, respectively. It is suggested that the lower preservation potential of organic matter could also be related to the Eocene volcanic activity in Sarawak. Â© 2021. All rights reserved.